La Ilustración Republicana Federal (1871-1872): Communicate the Republican Faith Through Image and Word - Rodríguez Vargas, Hernán (Hispania Nova, 2024)
La Ilustración Republicana Federal was an illustrated republican newspaper directed by Enrique Rodríguez-Solís, featuring the collaboration of prominent members of the Federal Democratic Republican Party. This collaboration, along with the newspaper’s period of circulation (1871-1872), renders it one of the most significant endeavors in disseminating republican pedagogy through the interplay of visual imagery and written texts. This article argues that, apart from being a potent tool for political promotion, the newspaper represented a sophisticated fusion of visual and narrative elements to propagate republican ideals, as noted by Fernando Garrido in the fifth edition of his Catecismo Republicano. Within this synthesis aimed at spreading and garnering popular consensus, the newspaper encompasses three crucial elements. Firstly, it brings together the figure of Marianne and the new republican symbolism, imbuing republicanism with dogmatic and ritualistic characteristics. Secondly, it emphasizes republicanism through the valorization of a new community of patriot-martyrs. Finally, through a public utilization of the past, it constructs a complex discourse that shapes the republican project in salvific and teleological terms, drawing upon diverse perspectives and interpretations of history. These elements, whether disseminated individually or collectively through texts, images, and objects, operated within a wider and intricate media framework, championed and defined by the collaborators, writers, and artists of La Ilustración Republicana Federal as «republican propaganda».
Keywords: Republic; republicanism; community of martyrs; public use of history; civil religion